Vanadium-containing modified clays as catalysts for acetaldehyde production by ethanol selective oxidation - Sabre, Ema Virginia (2024)
This work investigates use of natural clays as a sustainable raw material to prepare supported vanadium catalysts for the aerobic selective oxidation of ethanol to produce acetaldehyde. As dispersion and nature of the supported V species depend on its interaction with the support surface and its specific surface area, montmorillonite extracted from an Argentinian bentonite clay was pillared with titania, and vanadium was added by wet impregnation to get V/Ti-PILC catalysts. The effects of catalyst V content (0.5 – 2 wt%), reaction temperature (250 – 350 ºC) and O2/ethanol molar ratio (0.5 – 1.5) on their performance for this reaction were studied. Characterization by X-ray diffraction (XRD) and N2 adsorption/desorption isotherms showed that the synthesized catalysts maintained the mesoporous structure after the V addition, though their lamellar structure lost regularity. Under the reaction conditions explored, all the V/Ti-PILC catalysts were active and very selective to acetaldehyde (80 %), their activity increasing with V content. The highest activity was associated with the highest dispersion of isolated tetrahedral vanadium centers, identified by diffuse reflectance UV-Vis, Raman and X-ray photoelectron (XPS) spectroscopies. The highest ethanol conversion (87 %), with 85 % selectivity to acetaldehyde, was reached over the catalyst with 2 wt% of V at 350 ºC with O2/ethanol = 1. The acetaldehyde yield and selectivity values reached are comparable with those reported for related mesoporous catalysts, which allows to consider these supports a sustainable alternative for high surface area supported vanadium catalysts.